Design of cluster structure units with large surface areas for high-capacity hydrogen storage: In the case of Si12C12H24. (3rd August 2017) - Song, Bin; Zhang, Xiayan; He, Pimo; Zhao, Gaoling; Han, Gaorong
Abstract: Using density functional theory, we designed novel cluster structure units with large surface areas for hydrogen storage through the surface functionalization of a stable Si12 C12 H24 nanocage with CONH2 organic molecules and Li atoms. Two structures, namely, Si12 C12 H12 (CONHLi)12 and Si12 C12 H12 (CONLi2 )12, are proposed. The structures are stable at room temperature and show suitable hydrogen adsorption energies. Modification can enlarge the surface area of the two structures compared with the original cluster. In addition, the O and N anions participate in the adsorption of H2 molecules in addition to the Li cations. The average hydrogen binding energy for Si12 C12 H12 (CONHLi)12 ·82H2 is 0.135 eV/H2 and the average hydrogen binding energy for Si12 C12 H12 (CONLi2 )12 ·84H2 is 0.134 eV/H2 when these cluster structure units reach their maximum H2 uptake capacity. The gravimetric hydrogen percentages are 13.18 and 12.60 wt%, respectively. With such a structural unit, a suitable linker allows the assembly of metal organic framework-like porous materials that display satisfactory hydrogen storage properties at room temperature. Highlights: We design cluster structure units with large surface areas for hydrogen storage. A Si12 C12 H24 nanocage is modified by CONH2 organic molecules and Li atoms. Two structures of Si12 C12 H12 (CONHLi)12 and Si12 C12 H12 (CONLi2 )12 are proposed. The resulting structure units show high stability and H2 uptake capacity. Forming MOF-like frameworks by these structure units may improve their H2 uptake capacity further.